Step-by-step explanation:
Let's solve your equation step-by-step.
2(x+2)−3(x−3)=x+7
Step 1: Simplify both sides of the equation.
2(x+2)−3(x−3)=x+7
(2)(x)+(2)(2)+(−3)(x)+(−3)(−3)=x+7(Distribute)
2x+4+−3x+9=x+7
(2x+−3x)+(4+9)=x+7(Combine Like Terms)
−x+13=x+7
−x+13=x+7
Step 2: Subtract x from both sides.
−x+13−x=x+7−x
−2x+13=7
Step 3: Subtract 13 from both sides.
−2x+13−13=7−13
−2x=−6
Step 4: Divide both sides by -2.
−2x
−2
=
−6
−2
x=3
Answer:
x=3
Answer:
56
Step-by-step explanation:
8 * 7 = 56
<u>How many minutes does it take stewart to Drive to work? = 7 times</u> <u>8 minutes</u>
There are no solutuons listed (says which of the following). My answer below should be in the list to choose from.
7 - 4x ≥ 35
subtract 7 from both sides
-4x ≥ 28
divide both sides by -4 AND change the direction of the inequality sign because we're dividing by a negative
x ≤ -7
CHECK:
7 - 4x ≥ 35
7 - 4(-7) ≥ 35
7 + 28 ≥ 35
35 ≥ 35
ANSWER: x ≤ -7
Hope this helps! :)
The answer should be A. 4.5
Because line x is just over half of the length of the line that is 8ft
Hey there! I'm happy to help!
If you raise a fraction to an exponent, you apply that exponent to the numerator and the denominator. This would give us
.
Have a wonderful day! :D